2015 IEEE 12th International Conference on Mobile Ad Hoc and Sensor Systems 2015
DOI: 10.1109/mass.2015.86
|View full text |Cite
|
Sign up to set email alerts
|

New Directions in Content Centric Networking

Abstract: Abstract-We revisit some of the basic premises of the Content-Centric networking (CCN) and Named-Data Networking (NDN) architectures, which have been proposed as alternatives to the IP Internet architecture in order to support more efficient access to content available in the Internet. We address the large overhead incurred in NDN and CCN by maintaining forwarding state for each Interest traversing a router and for each content-name prefix known to each router. We introduce a new approach designed to provide o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Hence, independently of the type of name-based content routing used [45,51,57,99], the combined use of address-based routing and redirection schemes that map names to addresses can be done far more efficiently than the combined use of name-based routing and PIT's at each router. Performance results of recent ICN approaches based on addresses indicate that this is the case [46][47][48][49][50].…”
Section: Prior Icn Architecturesmentioning
confidence: 96%
“…Hence, independently of the type of name-based content routing used [45,51,57,99], the combined use of address-based routing and redirection schemes that map names to addresses can be done far more efficiently than the combined use of name-based routing and PIT's at each router. Performance results of recent ICN approaches based on addresses indicate that this is the case [46][47][48][49][50].…”
Section: Prior Icn Architecturesmentioning
confidence: 96%
“…We have recently proposed CCN-GRAM (Gathering of Routes for Anonymous Messengers) [12], [14] as an approach to Interest-based content-centric networking that eliminates the performance limitations resulting from using PITs in NDN and CCNx. We have shown that CCN-GRAM [14] substantially outperforms NDN by requiring orders of magnitude smaller forwarding state to deliver content while attaining similar endto-end delays.…”
Section: Introductionmentioning
confidence: 99%